2017
DOI: 10.1002/app.44894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of highly exfoliated montmorillonite layers on the properties of clay reinforced terpolymer nanocomposite plugging microspheres

Abstract: In this study, exfoliated montmorillonite (MMT) nanolayers were successfully encapsulated in acrylamide/acrylic acid/2acrylamido-2-methylpropanesulfonic acid (AM/AA/AMPS) terpolymer microspheres by in situ inverse suspension polymerization with the aid of the organic intercalation modification and the lateral groups of terpolymer chains. The introduction of well-dispersed MMT nanolayers reveals a significant enhancement of the comprehensive properties of these nanocomposite microspheres, such as the viscoelast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The organically intercalated montmorillonite (OMt) suspension was prepared according to a previously reported protocol. 24,25 In a three-necked ask, 3.0 g of pristine montmorillonite (Na-MMT) was dispersed in 100 mL of deionized water for 30 min. The intercalating agent G16-2-16 (0.4 g, equal to $0.27 CEC) was dissolved in 25 mL of deionized water before its addition to a threenecked ask and then stirred for 8 h at 80 C. To maintain the amphiphilicity of OMt and disperse it well in water, the amount of the cationic intercalant was set at 0.2 CEC; aer completion of the cation exchange reaction, a part of the OMt suspension was ltered and dried under vacuum for XRD measurement; the remaining OMt suspension sample (solid content ¼ 2.85% w/v) was sealed and stored for emulsion preparation.…”
Section: Preparation Of the Organically Intercalated Montmorillonite mentioning
confidence: 99%
“…The organically intercalated montmorillonite (OMt) suspension was prepared according to a previously reported protocol. 24,25 In a three-necked ask, 3.0 g of pristine montmorillonite (Na-MMT) was dispersed in 100 mL of deionized water for 30 min. The intercalating agent G16-2-16 (0.4 g, equal to $0.27 CEC) was dissolved in 25 mL of deionized water before its addition to a threenecked ask and then stirred for 8 h at 80 C. To maintain the amphiphilicity of OMt and disperse it well in water, the amount of the cationic intercalant was set at 0.2 CEC; aer completion of the cation exchange reaction, a part of the OMt suspension was ltered and dried under vacuum for XRD measurement; the remaining OMt suspension sample (solid content ¼ 2.85% w/v) was sealed and stored for emulsion preparation.…”
Section: Preparation Of the Organically Intercalated Montmorillonite mentioning
confidence: 99%
“…However, there were no obvious diffraction peaks found for OMMT/HBPA at 2θ = 2-10°. From literature, it was observed that if the MMT was completely exfoliated into individual and collapsed silicate layers, the regular crystalline structure cannot be found from the XRD patterns ( Ji et al 2017;Osman et al 2017;Xu et al 2019a). From Figure 1a, it was observed that there were some small peaks at 25°, 32°, and 34°.…”
Section: Characterization Of Ommt/hbpa Emulsionmentioning
confidence: 97%
“…However, natural Na-MMT is hydrophilic because of the presence of Na + and K + ions between its layers. Therefore, in order to increase the compatibility of MMT platelets with hydrophobic polymer bulk, the original MMT needs to carry out organic pre-modification by cation exchange technology [34,38]. Many previous studies have indicated the organic MMT is easier for achieving homogeneous dispersion and exfoliation in the polymer matrix [36,39].…”
Section: Introductionmentioning
confidence: 99%